2001
DOI: 10.1007/s0026702409
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Urbanization on Stream Habitat and Fish Across Multiple Spatial Scales

Abstract: We analyzed the relation of the amount and spatial pattern of land cover with stream fish communities, in-stream habitat, and baseflow in 47 small southeastern Wisconsin, USA, watersheds encompassing a gradient of predominantly agricultural to predominantly urban land uses. The amount of connected impervious surface in the watershed was the best measure of urbanization for predicting fish density, species richness, diversity, and index of biotic integrity (IBI) score; bank erosion; and base flow. However, conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
392
2
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(426 citation statements)
references
References 32 publications
24
392
2
8
Order By: Relevance
“…The ecotones are responsible for the reduction of agricultural run off. They also serve for fish as foraging areas and provide shelter against predators (Zalewski et al 1995, Penczak 2001, Wang et al 2001. The availability of spawning and nursery grounds has been reduced because neighbouring areas are not flooded in spring (Bayley 1995, Kubečka & Vostradovský 1995, Ligon et al 1995, Jurajda et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The ecotones are responsible for the reduction of agricultural run off. They also serve for fish as foraging areas and provide shelter against predators (Zalewski et al 1995, Penczak 2001, Wang et al 2001. The availability of spawning and nursery grounds has been reduced because neighbouring areas are not flooded in spring (Bayley 1995, Kubečka & Vostradovský 1995, Ligon et al 1995, Jurajda et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Fitzpatrick et al (2001) found that increasing forest cover had a negative effect on fish taxon diversity and increasing nutrient concentrations had a positive effect. Wang et al (2001) also found that an increasing percentage of agricultural land use increased fish taxon diversity, while Harding (2003) and Mensing et al (1998) found that increasing non-natural catchment land use led to a reduction in taxon diversity. When studying the direction of the relationships with the IBI scores (lower part of Table 1) these contradictory results were not found.…”
Section: Exploring Relationshipsmentioning
confidence: 99%
“…Thus, larger streams (high-order streams) located in downstream regions were largely impacted by the ecological health, compared to the references streams (An et al 2004). These circumstances are frequently reported in urban streams, which are directly impacted by discharge waters from WDPs or/and industrial complex (Wang et al 2001).…”
Section: M -Ibi Model and Habitat Healthmentioning
confidence: 99%